Autonomous Electrification: A Paradigm Shift in Urban Transportation Dynamics - R., S.R. Krishnam Naidu (International Journal of Psychosocial Rehabilitation, 2020)
The shift towards autonomous electrification marks a transformative phase in urban transportation dynamics. This research explores the intersection of autonomous vehicle technology and electrification, aiming to understand their collective impact on urban mobility. The paper synthesizes existing literature on urban transportation challenges, environmental concerns, and technological advancements to provide a comprehensive overview of the subject. Methodologically, the research employs a data-driven approach, utilizing case studies and analysis of real-world projects to assess the integration of autonomous and electric technologies. The investigation into autonomous vehicle technology covers various levels of autonomy, key components, and ongoing developments. Similarly, the electrification section outlines the benefits of electric vehicles, infrastructure requirements, and sustainability considerations. The paper then delves into the intricate relationship between autonomous and electric technologies, exploring synergies, challenges, and potential solutions. Real-world case studies illustrate successful implementations and offer insights into challenges faced. The research also discusses the evolving urban transportation dynamics, including changes in traffic patterns, impacts on public transportation, and implications for urban planning. Despite the promising prospects, the paper acknowledges and analyzes existing barriers such as regulatory hurdles, public acceptance, and technological limitations. The concluding section summarizes key findings, discusses future prospects, and emphasizes the significance of this paradigm shift in shaping the future of urban transportation.